Implementation of the Optical Flow to Estimate the Propagation of Eddies in the South Atlantic Ocean - Denis L. Volkov; Shahriar Negahdaripour (Remote Sensing, 2023)
The ocean is filled with mesoscale eddies that account for most of the oceanic kinetic energy. The importance of eddies in transporting properties and energy across the ocean basins has led to numerous efforts to track their motion. Here, we implement a computer vision technique—the optical flow—to map the pathways of mesoscale eddies in the South Atlantic Ocean. The optical flow is applied to the pairs of consecutive sea surface height maps produced from a nearly 30-year-long satellite altimetry record. In contrast to other methods to estimate the eddy propagation velocity, the optical flow can reveal the temporal evolution of eddy motion, which is particularly useful in the regions of strong currents. We present the time-dependent estimates of the speed and direction of eddy propagation in the Eulerian frame of reference. In an excellent agreement with earlier studies, the obtained pattern of eddy propagation reveals the interaction of eddies with the background flow and the bottom topography. We show that in the Antarctic Circumpolar Current, the variability of the eddy propagation velocity is correlated with the variability of the surface geostrophic velocity, demonstrating the robustness of the optical flow to detect the time-variable part of eddy motion.